Metabolic profile And Clinical Management Of PosPartum Udder Oedema In dairy Cattle - Venkatesa Kumar E (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2000)
A study was conducted in the Department of Clinical Medicine, College of Veterinary and Animal Sciences, Mannuthy for a period of three semesters, during the year 1999 to 2000, to elucidate the etio-pathogenesis of the udder oedema in crossbred cows. The study included haemogram, metabolic profile test, urinalysis, udder measurements and comparison of the efficacy of treatments with Tribulus terreslris Linn and frusemide in udder oedema cases. Twenty crossbred cows with persistent udder oedema were selected. Four cows developed mastitis during the observation period. The remaining sixteen animals were randomly divided into two groups viz. Giroup I with seven animals which were treated with frusemide and Group 11 with nine animals which were treated with Tribulus terrestris Linn. Six apparently healthy cows maintained under identical conditions served as the control group. Udder oedema occurred mostly in first two calvings around pen- parturient period. The affected animals were clinically normal except for the involvement of udder. Oedema extended mostly upto umbilicus, pale to pinkish in colour, cold to touch, pitting on pressure and was painful. Oedema extending to the base of the teats and shortening of teats were also observed. In the present study, haemagalactia, mastitis and maggot wound on the udder were observed as complications of udder oedema. The sole haematological change observed in udder oedema cases was an increase in mean corpuscular volume (MCV). The serum biochemical estimation showed a decrease in the serum inorganic phosphorus value of cows with udder oedema when compared to control cows. The post-treatment serum biochemical values showed a decrease in serum potassium in frusemide treatment and an increase in serum glucose in Tribulus terrestris Linn treatment.